Understanding the Cellular Origin of the Mononuclear Phagocyte System Sheds Light on the Myeloid Postulate of Immune Paralysis in Sepsis - Poulin, Lionel Franz; Lasseaux, Corentin; Chamaillard, Mathias (Frontiers in Immunology, 2018)
Sepsis, in essence, is a serious clinical condition that can subsequently result in death as a consequence of a systemic inflammatory response syndrome including febrile leukopenia, hypotension and multiple organ failures. To date, such life-threatening organ dysfunction remains one of the leading causes of death in intensive care units, with an increasing incidence rate worldwide and particularly within the rapidly growing senior population. While most of clinical trials are aimed at dampening the overwhelming immune response to infection that spreads through the bloodstream, based on several human immunological investigations it is now widely accepted that susceptibility to nosocomial infections and long-term sepsis mortality involves an immunosuppressive phase that is characterized by a decrease in some subsets of dendritic cells. Only recently have substantial advances been made in terms of the origin of the mononuclear phagocyte system that is now likely to allow for a better understanding of how the paralysis of dendritic cells leads to sepsis-related death. Indeed, the unifying view of each subset of dendritic cells has already improved our understanding of the pivotal pathways that contribute to the shift in commitment of their progenitors that originate from the bone marrow. It is quite plausible that this anomaly in sepsis may occur at the single level of dendritic cell-committed precursors, and elucidating the immunological basis for such a derangement during the ontogeny of each subset of dendritic cells is now of particular importance for restoring an adequate cell fate decision to their vulnerable progenitors. Last but not least, it provides a direct perspective on the development of sophisticated myelopoiesis-based strategies that are currently being considered for the treatment of immunosenescence within different microenvironments, such as the kidney and the spleen.